History of depression through the ages - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2020)
Depressive thoughts appeared from the origins of Humanity. They are found in philosophical writings and in literature since Antiquity. They have been approached in a religious or medical way since always, with conceptions which sometimes mixed physiological and mystical explanations. With the advent of psychiatry as a medical discipline, depressive disorder was included in the classifications of mental disorders. In the first half of the 20th century, depression was only a detectable syndrome in most mental illnesses, psychoses and neuroses, and received no special attention in our societies. Its determinism is designed in a multifactorial way, integrating psychological, social and biological factors.